(untitled) (Revista Paradigma, 2019)
The present work perpasses the different positions adopted by the Federal Supreme Court in relation to the crime of drug trafficking, especially the small trafficking, described in article 33, paragraph 4, of Law 11.343, of August 23, 2006. It is observed continuous ruling of the Court in order to reduce the public punitive power that falls over the last figure. On the other hand, the reasons for ruling of the Federal Supreme Court seem, more and more, to resemble public policies, distancing itself from the traditional role -a mechanical role on would say- of judges as a "mouth of the law." Notwithstanding the denial of simple application of the law, it opens up a field of difficult legal, institutional and social control, that is, a wide and broad interpretative freedom in the exercise of constitutional jurisdiction. Hence a frank approximation of Federal Supreme Court judgments to discretionary administrative acts, specially in this suffered field of illegal drug trafficking.